PENGARUH KEPUTUSAN INVESTASI DAN KEPUTUSAN PEMBIAYAN TERHADAP ALIRAN KAS BEBAS PADA PERUSAHAAN JASA KONSTRUKSI YANG TERDAFTAR DIBURSA EFEK INDONESIA) - Tasum SE., M.Si (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2017)
This study aims to determine how the effects of financing decisions investasi.dan decision to free cash flow as the dependent variable.The object of research is a building construction company listed on bei as population and sampling technique used purposive sampling and there are six (6) companies that meet the criteria. The study period was 2007 s.d. 2010. Data were analyzed using descriptive analysis and kuantitative withmultiple regression model. From the test results are statistically independent variable investment decisions and financing decisions either simultaneously or partially significant effect on free cash flow is a construction services company listed on the Stock Exchange. Investment decisions have a positive correlation and financing decisions have a negative correlation with free cash flow of building construction services company listed on the Stock Exchange. Free varabel ability to explain the change of variables terika large cash flow amounted to 41.80% and the remaining 58.20% influenced by other factors beyond the variables analyzed